SUITABILITY ANALYSIS OF FLOATING CAGE CULTURE OF GROUPER FISH USING GIS IN RINGGUNG WATERS OF LAMPUNG - Indah Febry Hastari; Rahmat Kurnia; M. Mukhlis Kamal (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2017)
The study aims to determine suitability of floating cage (KJA) culture of grouper fish in Ringgung waters of Lampung. Data were analysed using GIS for spatial analysis at five stations.  There were 10 water quality parameters measured, such as bathimetry, current velocity, water transparency, temperature, salinity, pH, dissolved oxygen, nitrate, ammonia, and phosphate. Three suitability criteria, i.e very suitable, suitable, and not suitable were used to determine the suitability of floating cage culture of grouper fish. The results show that from 99.168,5 ha of the total area used for floating cage culture of grouper fish, about 85,94% covering 8522,16 ha were classified as very suitable, 5,64% covering 559,69 ha classified as suitable, and  8,42% covering 835 ha classified as not suitable.                                     Keywords : grouper culture, suitability, Ringgung waters, Lampung Province, GIS